Influence of the Mineral Content on the Emissivity of Hydrothermal Char. Issue 5 (31st March 2020) - Graeser, Philipp; Pörtner, Lukas; Schiemann, Martin
Abstract: The influence of minerals on solid fuel conversion is an important topic and has so far been addressed focusing mainly on the catalytic effects. Here, the impact of iron oxide on the emissivity of burning char particles was investigated. Synthetic, hydrothermally carbonized char was doped with SiO2 or with a mixture of SiO2 and Fe2 O3 . The sample was then exposed to an oxy‐fuel atmosphere in a laboratory reactor. An established pyrometer/infrared (IR) spectrometer setup was used to measure the size, temperature, and IR radiation of single burning particles. Based on these measurements, the spectral and total emissivity in the near‐IR (1.25–2.25 μm) and the total emissivity in the mid‐IR region (2.4–5.5 μm) were calculated. The results show that the iron content directly influences the emissivity of char during combustion. Abstract : The emissivity of burning particles of synthetic char is presented. Particles in the size of 100 μm were measured in‐flight with a special test rig. The results show that mineral doping with SiO2 or a mixture of SiO2 and Fe2 O3 affects the char emissivity, clarifying the contributions of specific minerals to the char emissivity.